Human body's channel modeling and low power, high data rate transceiver design for wireless capsule endoscopy - Md. Rubel, Basar (Universiti Malaysia Perlis (UniMAP), 2014)
Ingestible wireless capsule endoscopy (WCE) is one and only the painless effective novel diagnostic technology for inspecting entire gastrointestinal (GI) track diseases. But some major limitations, poor image resolution, limited working time and unable to repeated view of critical area confine the wider application of this technology. For the further development of WCE, the main concern is the development of a low power and high-speed telemetry system that is capable of transmitting high-resolution images at a higher frame rate. In this regard, this thesis report on investigation of path loss and its variation in human body channel with high performance transceiver (transmitter and receiver) design. To investigate the path loss in the body channel, a heterogeneous human body model was used, which is more comparable to the human body than a homogenous model. The finite integration technique (FIT) in Computer Simulation Technology’s (CST’s) Microwave Studio was used in the simulation. The path loss was analyzed in the frequency range of 100 MHz to 2450 MHz. The path loss was found to be saliently lower at frequencies below 900 MHz. The smallest loss was found around the frequency of 450 MHz, where the variation of path loss throughout the GI tract was 29 dB, with a minimum of -9 dB and a maximum of -38 dB. However, at 900 MHz, this variation was observed to be 38 dB, with a minimum of -10 dB and a maximum of -48 dB. The path loss was comparatively higher during examination of anatomically-complex regions, such as the upper intestine and the lower esophagus as compared to the less complex stomach and upper esophagus areas. Therefore, it is recommended that the spectrum centralized at 450 MHz should be the optimum selection in favour of smallest path loss. Finally, a highly efficient direct modulation transmitter and a digitalized RF analog to digital conversion receiver, both of supporting the data rate up to 100 Mbps, have been designed in Advanced Design System (ADS) at 450 MHz. The transmitting path consists only a low power oscillator, an envelope filter and a matching network. The entire transmitter circuit draws average 2 mA current from a 1.5 V DC supply. The start-up transient period of oscillator is optimized to less than 6 ns to support digital data transmission at the rate of 100 Mbps. On the other hand, the receiver is implemented using a low noise amplifier (LNA), logarithmic amplifier (LA), power detector and comparator. The LNA and the three stages LA provide the gain 80 dB which makes able the receiver sense the input weak signal up to the level -80 dBm.